Analisis Pengaruh Indeks Kesehatan dan Indeks Pendidikan, Angkatan Kerja dan Jumlah Penduduk Terhadap IPM di Provinsi Jawa Timur Tahun 2015-2021 - Elsa Nova Aryanti (Jurnal Ilmu Ekonomi, 2023)
This study aims to analyze the effect of the human development index which consists of the education and health index variables, the labor force, and the population in East Java Province in 2015 – 2021. The data used in this study uses panel data with time series for the last seven years from 2015 – 2021 with thirty eight regencies/cities in East Java Province. The best regression results using a random effect model. where the results show that the variable level of education, health and workforce have a positive and significant effect, and the variable population size has a negative and significant effect on the HDI of districts/cities in East Java province.